Squeezing Size and Weight into Human Rights Laws: The Case for a Ground that Fits - Szczurko, Megan (Canadian Woman Studies/les cahiers de la femme, 2023)
The Ontario Human Rights Code provides legal protection against discrimination in the social areas of employment, membership, services, contracts, and housing based on several protected grounds. Contrary to popular fatphobic myths, re-search demonstrates that fatness is a characteristic that is either immutable or mutable only at great personal cost. Although fat people experience group disadvantage analogous to that associated with protected grounds like sex, race, and religion, “weight or size” is not a prohibited ground of discrimination under the Code. Fatphobia is a social justice issue and the Code must be amended to include “weight or size” as a prohibited ground. Legislative change is necessary to affirm the inherent dignity and worth of fat people and ensure that people of all sizes can participate as equals in their communities.